Temporal Analysis of Photo‐Thermally Induced Reconfigurability in a 1D Gold Grating Filled with a Phase Change Material. Issue 2 (10th November 2021) - Zamani, Naser; Hatef, Ali; Nadgaran, Hamid
Abstract: In this study, the finite‐element method is used to numerically calculate a photo‐thermally induced reconfigurability in a 1D gold grating structure filled with the phase change material Ge2 Sb2 Se4 Te1 (GSST). GSST features a reversible and stable phase change between amorphous and crystalline phases around a critical temperature of 410 K with broadband low optical loss. In this study, the required heating for the transition between phases is provided by a nanosecond Gaussian pulse laser through a photo‐thermal absorption process. A comprehensive heat transfer analysis is performed to investigate the thermal characterizations of the proposed structure. The results show that in the amorphous state, the structure has a near unity absorption band in the infrared region. As the temperature increases during the pulse, the GSST undergoes the amorphous to crystalline phase change. In the intermediate states (partial crystallization) of the GSST two resonance peaks are excited and the absorption finally reaches its minimum value of 0.2 in the GSST crystalline phase. The findings of this study not only provide the fundamental concepts for the suggested tunable structure, but also have potential applications in a variety of nanophotonic devices including thermal emission controllers, sensors, and optical detection devices. Abstract : An absorber based on 1D gold grating filled by Ge2 Sb2 Se4 Te1 (GSST) as a phase change material is proposed. The required temperature for the switching between the amorphous and crystalline phases is provided by a nanosecond Gaussian pulse laser through photo‐thermal absorption process. It is shown that GSST controls the effect of the distribution of plasmonics modes on a lossy heat source.